2018
DOI: 10.1007/s00394-018-1703-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of the microbiome for human health: from basic science to clinical applications

Abstract: The 2017 annual symposium organized by the University Medical Center Groningen in The Netherlands focused on the role of the gut microbiome in human health and disease. Experts from academia and industry examined interactions of prebiotics, probiotics, or vitamins with the gut microbiome in health and disease, the development of the microbiome in early-life and the role of the microbiome on the gut–brain axis. The gut microbiota changes dramatically during pregnancy and intrinsic factors (such as stress), in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
260
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(272 citation statements)
references
References 117 publications
(138 reference statements)
1
260
0
11
Order By: Relevance
“…CS-A and CS-C are both composed of repeating disaccharide units composed of D-glucuronic acid (GlcA) and N-acetyl-D-galactosamine (GalNAc). GlcA is linked β (1,3) to GalNAc which is then linked β (1,4) to the next GlcA. CS-A and CS-C differ only in sulfation with CS-A highly enriched in O4 sulfation on GalNAc whilst CS-C is enriched in O6 sulfation on GalNAc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CS-A and CS-C are both composed of repeating disaccharide units composed of D-glucuronic acid (GlcA) and N-acetyl-D-galactosamine (GalNAc). GlcA is linked β (1,3) to GalNAc which is then linked β (1,4) to the next GlcA. CS-A and CS-C differ only in sulfation with CS-A highly enriched in O4 sulfation on GalNAc whilst CS-C is enriched in O6 sulfation on GalNAc.…”
Section: Resultsmentioning
confidence: 99%
“…CS-A and CS-C differ only in sulfation with CS-A highly enriched in O4 sulfation on GalNAc whilst CS-C is enriched in O6 sulfation on GalNAc. DS is related to CS-A except GlcA is predominantly replaced with L-iduronic acid which is connected to GalNAc via an α (1,4) linkage. Finally, HA is similar to CS-A but replaces GalNAc with N-acetyl-D-glucosamine (GlcNAc) and contains no sulfation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, intermittent fasting prevents diabetic retinopathy by restructuring the gut microbiota (22) . Other publications link therapeutic effects of fasting to changes of gut microbiota in patients with rheumatoid arthritis (23,24) . Only one study performed in human subjects showed that after 1…”
mentioning
confidence: 99%
“…Research shows the great importance of a healthy microbial composition in the gut at an early stage in life (2-3 years of age), a period also characterized by an intense neurodevelopment in humans. Several reports conclude that early gut dysbiosis can influence the neurodevelopment in the short run and may also lead to mental health issues later in life [4,5].…”
Section: Introductionmentioning
confidence: 99%